THE IMPORTANCE OF PRONUNCIATION TECHNIQUES TO HELP STUDENTS IMPROVE THEIR SPOKEN ENGLISH (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT For language educators and learners, pronunciation is one of the most important skills to master. It plays a pivotal role in helping students communicate effectively and its impact goes way beyond just speaking correctly. This blog post highlights and explores the best methods for teaching pronunciation, identifies why they work and provides practical examples that language teachers can use in their language classrooms to inspire and support students. Getting pronunciation right boosts speakers’ confidence and fluency, reduces miscommunication and prepares learners for real-life conversations.